Comparative kinetic modeling of growth and molecular hydrogen overproduction by engineered strains of Thermotoga maritima. (15th March 2019) - Singh, Raghuveer; Tevatia, Rahul; White, Derrick; Demirel, Yaşar; Blum, Paul
Abstract: Thermotoga maritima is an anaerobic hyperthermophilic bacterium known for its high amounts of hydrogen (H2 ) production. In the current study, the kinetic modeling was applied on the engineered strains of T. maritima that surpassed the natural H2 production limit. The study generated a kinetic model explaining H2 overproduction and predicted a continuous fermentation system. A Leudking-Piret equation-based model predicted that H2 production by Tma200 (0.217 mol-H2  g −1 -biomass) and Tma100 (0.147 mol-H2  g −1 -biomass) were higher than wild type (0.096 mol-H2  g −1 -biomass) with reduced rates of maltose utilization. Sensitivity analysis confirmed satisfactory fitting of the experimental data. The slow growth rates of Tma200 (0.550 h −1 ) and Tma100 (0.495 h −1 ) are compared with the wild type (0.663 h −1 ). A higher maintenance energy along with growth and non-growth H2 coefficients corroborate the higher H2 productivity of the engineered strains. The modeled data established a continuous fermentation system for the sustainable H2 production. Graphical abstract: Image 1 Highlights: Hydrogen (H2 ) synthesis was studied in engineered strains (ES) of Thermotoga maritima. Kinetic modeling determined the correlation between metabolites and growth. The p-type metabolism in ES produced more H2 than the q-type metabolism in wild type. Carbon rerouting increased maintenance energy to yield H2 beyond 4 mol mol −1 hexose. Continuous hydrogen production was simulated for sustainable hydrogen production.